Da pedagogia do jogo ao voleibol sentado: possibilidades inclusivas na Educação Física Escolar; Inclusão - Miron, Edison Martins (2011)
Sport is one of the most developed contents in physical education classes in schools; nevertheless, it doesn‟t get the necessary pedagogical treatment for its better use as an educational instrument. In order to be truly democratic, it has to be adapted to the students needs and possibilities. Volleyball as a team sport creates confrontational and cooperative situations that can be done in a pedagogical way by the teacher. With the same objective and dynamics, the adapted sport Sitting Volleyball is able to facilitate positive actions in interpersonal relations, in which the possibility of success during school sports development may be more evident among students with and without physical disabilities. The present study aimed to systematize, put into practice and analyze a teaching program conceived to teach sitting volleyball to students with physical disabilities through games played in a sitting position, as a strategy to sensitize people to include physically disabled students in physical education classes at elementary school. From a pedagogical focus, the development of this study was supported by quantitative approach theoretical references and it is configured as a case study. The study was conducted in public schools of a medium-sized country town of São Paulo state. There were 120 participants from the fifth and sixth grades at elementary school, from three different groups of physical education classes with at least one physically disabled student included in each group. The instruments used for data collection were: a) observation protocol; b) beginning and ending questionnaire. In every class there was also the Field Notes filling to support the data quantitative analysis. The data collected and analyzed showed that in 98% of the developed activities, the possibilities of interpersonal relationship happened in a positive way among students with and without physical disabilities, promoting joint participation in conditions and possibilities of similar success that aroused concepts and values which enabled the accomplishment of the inclusive work.